NASA formal methods : 8th International Symposium, NFM 2016, Minneapolis, MN, USA, June 7-9, 2016, Proceedings /: 8th International Symposium, NFM 2016, Minneapolis, MN, USA, June 7-9, 2016, Proceedings. (2016) - Unknown
No abstract available